Mycobacterium tuberculosis and whole genome sequencing: a practical guide and online tools available for the clinical microbiologist. (February 2017) - Satta, G.; Atzeni, A.; McHugh, T.D.
Abstract: Whole genome sequencing (WGS) has the potential to revolutionize the diagnosis of Mycobacterium tuberculosis infection but the lack of bioinformatic expertise among clinical microbiologists is a barrier for adoption. Software products for analysis should be simple, free of charge, able to accept data directly from the sequencer (FASTQ files) and to provide the basic functionalities all-in-one. The main aim of this narrative review is to provide a practical guide for the clinical microbiologist, with little or no practical experience of WGS analysis, with a specific focus on software products tailor-made for M . tuberculosis analysis. With sequencing performed by an external provider, it is now feasible to implement WGS analysis in the routine clinical practice of any microbiology laboratory, with the potential to detect resistance weeks before traditional phenotypic culture methods, but the clinical microbiologist should be aware of the limitations of this approach.